2016
DOI: 10.1152/jn.00090.2016
|View full text |Cite
|
Sign up to set email alerts
|

A dual-learning paradigm can simultaneously train multiple characteristics of walking

Abstract: Impairments in human motor patterns are complex: what is often observed as a single global deficit (e.g., limping when walking) is actually the sum of several distinct abnormalities. Motor adaptation can be useful to teach patients more normal motor patterns, yet conventional training paradigms focus on individual features of a movement, leaving others unaddressed. It is known that under certain conditions, distinct movement components can be simultaneously adapted without interference. These previous "dual-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 40 publications
1
30
0
1
Order By: Relevance
“…Our study contributes to recent efforts to unveil the potential interaction between explicit corrections and implicit sensorimotor recalibration in locomotion (Malone et al, 2012; Long et al, 2016; Roemmich et al, 2016; Statton et al, 2016; Maeda et al, 2017). Interestingly, we found that preventing foot adjustments during split-belt walking significantly reduced post-adaptation effects compared to the control group.…”
Section: Discussionmentioning
confidence: 52%
“…Our study contributes to recent efforts to unveil the potential interaction between explicit corrections and implicit sensorimotor recalibration in locomotion (Malone et al, 2012; Long et al, 2016; Roemmich et al, 2016; Statton et al, 2016; Maeda et al, 2017). Interestingly, we found that preventing foot adjustments during split-belt walking significantly reduced post-adaptation effects compared to the control group.…”
Section: Discussionmentioning
confidence: 52%
“…The visual feedback simply provided an additional channel of performance feedback that was used for voluntary correction. However, our prior work showed that visual feedback can drive gait adaptation when a visual prediction error is present, such as showing one leg flexing less than it actually does [29]. Participants adapted to that visual feedback by increasing flexion in the perturbed leg and subsequently showed aftereffects when the visual perturbation was removed.…”
Section: Discussionmentioning
confidence: 99%
“…Our study contributes to recent efforts to unveil the potential interaction between explicit corrections and implicit sensorimotor recalibration in locomotion (Statton et al, 2016; Roemmich et al, 2016; Long et al, 2016; Malone et al, 2012; Maeda et al, 2017). Interestingly, we found that preventing foot adjustments during split-belt walking significantly reduced post-adaptation effects compared to the control group.…”
Section: Discussionmentioning
confidence: 73%